Cues for odor naming affect performance and brain connectivity - Capkan, Eda Nur; Yildirim, Funda (Frontiers in Human Neuroscience, 2025)
Human olfactory perception and naming represent a complex example of multisensory integration, with growing interest in how cues from different modalities affect olfactory recognition and naming. While studies show that visual cues may support odor naming performance, little is known about how cueing and multisensory integration in odor naming tasks influence neural mechanisms. This study examined the cognitive mechanisms underlying odor identification and the effect of two visual cue types—lexical and color—using behavioral and EEG methods. It also investigated the impact of hedonic ratings, Tip of the Nose phenomenon, familiarity, and subjective recall experiences on odor naming. Forty participants took part in an odor identification task using Sniffin’ Sticks. For each trial, an odorant was first presented, followed by either a visual cue (a color patch associated with the odor source) or a lexical cue (a word fragment). Participants were then asked to name the odor. To examine the neural mechanisms involved in cue-assisted odor identification, the time window during odor naming after the visual cue presentation was analyzed. Connectivity analysis and behavioral performance were assessed to evaluate the effectiveness of the different cue types in supporting identification. Behavioral findings showed that lexical cues improved identification accuracy. Furthermore, hedonic ratings, familiarity, and experiences related to the TON were found to significantly affect naming performance. Odor familiarity and liking levels affected both response accuracy and response time, with more familiar and liked odors being identified both more accurately and more quickly. Granger causality analysis revealed that the color cue condition exhibited more numerous and stronger network connections compared to the lexical cue condition. The lexical cue condition demonstrated more restricted network activation with fewer connections, utilizing focused frontal-temporal and frontal-parietal circuits. In both conditions, prefrontal regions served as strong control hubs, and language networks were preserved. However, additional frontal-occipital connections were observed in the color cue condition, in the form of interhemispheric coordination and visual system integration. The findings demonstrated that cross-modal odor naming utilizes different neural connections depending on cue type, with lexical cues showing more direct access to linguistic areas while color cues exhibit more complex connectivity patterns.